4th International Pipeline Conference, Parts a and B 2002
DOI: 10.1115/ipc2002-27168
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pipeline Diameter Variation on the Mixing Volume in Batch Transfers

Abstract: Presented in this paper is a new model for estimating mixing volumes arising in batch transfers in multiproduct pipelines, when variations of the line diameter as well as injection and/or withdrawal of products are present. Besides these novel features, the model incorporates the flow rate variation with time and the use of a more precise effective dispersion coefficient, which is considered to depend on the concentration. The governing equations of the model form a non-linear initial-value problem that is sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.The above research shows that the viscosity difference is the main factor that causes the tail of contamination, but these studies do not consider the special situations,such as dead-legs in a valve chamber, and are not closely integrated with practical engineering.…”
Section: Introductionmentioning
confidence: 99%